Bifocal type 2 segmental neurofibromatosis. - Garofalo, L. (European Journal of Pediatric Dermatology, 2009)
As in other autosomal dominant diseases, even in NF1 segmental lesions can be present (1, 2, 3, 4). The latter can arise on normal skin (type 1 segmental NF1) or in the context of generalized NF1 (type 2 segmental NF1). In the latter event the segmental lesions are severer and earlier than in the rest of the skin. Type 1 segmental NF1 is due to a post-zygotic mutation arising in a normal subject. On the other hand, type 2 segmental NF1 is due to a post-zygotic mutation arising in a subject with NF1, with consequent loss of heterozygosity and homozygosis in the affected segment. In the case here reported we are facing NF1 with type 2 segmental lesions affecting two -left mandibular and right gluteal- segments.